The Effect of Transformational Leadership and Remote Working on Employee Performance During COVID-19 Pandemic - Meiryani,; Nelviana,; Koh, Yorick; Soepriyanto, Gatot; Aljuaid, Mohammed; Hasan, Fakhrul (Frontiers in Psychology, 2022)
The Covid-19 outbreak has emphasized the importance of leadership style in achieving organizational performance. It also implies changes in administrative processes to remote working, impacting employee activities and performance. Employee performance is one of the aspects that might influence a company's success. If employees are productive and provide high-quality work, the company's performance will increase. This study aims to analyze the effect of Transformational Leadership and Remote Working on Employee Performance during the covid-19 pandemic. This study was conducted by performing a questionnaire distribution survey and acquiring 136 respondents. The research was conducted on a Jakarta area company that had implemented Remote Working. The number of samples in this study was determined using a simple random sampling procedure, in which the sampling was done at random without consideration for the population's existing strata. Data analysis was carried out using the SPSS 25 application. The analysis results show that Transformational Leadership has no significant impact on Employee Performance during the COVID-19 pandemic, and Remote Working has a significant impact on Employee Performance during the Covid-19 pandemic.